Efficacy and Safety of Intravenous Thrombolysis Beyond 4.5 Hours in Ischemic Stroke: A Systematic Review and Meta-Analysis - Muhammad Ahmad; Chavin Akalanka Ranasinghe; Mais Omar Abu-Sa’da; Durga Prasad Bhimineni; Muhammed Ameen Noushad; Talal Warsi; Ahmad Mesmar; Munikaverappa Anjanappa Mukesh; Sagar K. Patel; Gabriel Imbianozor; Ali Mustansir Bhatty; Ahmad Alareed; et al. (Diagnostics, 2025)
Background: Intravenous thrombolysis (IVT) is the standard treatment for ischemic stroke within 4.5 h of symptom onset. However, a significant proportion of patients present beyond this window. This study aims to evaluate the efficacy and safety of IVT beyond the 4.5 h window in selected patients. Methods: A systematic literature search was conducted across PubMed, Cochrane Library, and Google Scholar from inception to April 2025. Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled using a random-effects model. Results: A total of 12 RCTs were included, with 3236 patients. Compared to controls, IVT significantly improved excellent functional outcomes [OR: 1.40; 95% CI: 1.21–1.62] and good functional outcomes [OR: 1.26; 95% CI: 1.06–1.50] at 90 days. IVT also improved recanalization [OR: 2.47; 95% CI: 1.96–3.12], reperfusion [OR: 2.20; 95% CI: 1.26–3.84], and early neurological improvement [OR: 1.91; 95% CI: 1.12–3.26]. However, it was associated with a significantly higher risk of symptomatic intracranial hemorrhage (sICH) [OR: 2.17; 95% CI: 1.25–3.79], any ICH [OR: 1.49; 95% CI: 1.09–2.04], and type-II parenchymal hemorrhage (PH) [OR: 2.14; 95% CI: 1.19–3.83]. No significant difference was observed in systemic hemorrhage, 90-day all-cause mortality, 7-day mortality, or 90-day intervention-related mortality (p > 0.05). Conclusions: IVT beyond 4.5 h improves neurological outcomes in patients with ischemic stroke without increasing overall mortality or systemic bleeding, though it raises the risk of sICH, any ICH, and type-II PH. Further large RCTs are needed to confirm these findings and guide clinical practice.